PENGETAHUAN KESEHATAN REPRODUKSI REMAJA MELALUI PENDIDIKAN KELUARGA - Farihah Farihah (JURNAL KELUARGA SEHAT SEJAHTERA, 2015)
ABSTRACTIndonesia is expected to receive a demographic bonus in the year 2020-2030, that Indonesia will have a number of productive age population is about 2/3 of the total population. One aspect to consider in welcoming demographic bonus is preparing youth by giving them knowledge about health repsroduksi through family education. Family is the oldest educational institutions, informal, first and foremost dialamai by children as well as educational institutions that are natural. Therefore, education is a shared responsibility between families, communities and governments. As embodied dalan UUSPN 2003 chapter 1 verse 10 and 13, even the Ministry of Education and Culture (Kemendikbud) newly formed Directorate of Family Education. (PerMendikbud No. 11/2015 as a follow-up to PerPres No. 14/2015). This new Directorate will also be developing program of harassment or bullying, working with youth education, strengthening student achievement, personality and character education, life skills, drugs, and HIV / AIDS in order to become stronger Indonesian family. Kata Kunci : Kesehatan reproduksi, pendidikan keluarga.